HISTORICAL CONTEXT OF MANAGERIAL DECISIONS IN RUSSIAN SCIENCE AND HIGHER EDUCATION - Vladimir S. Diev (Moscow Polytechnic University, 2016)
The key theme of the paper is managerial decision making process in Russian academic science and higher school. The author states that education and science have an international character but also have a domestic specificity resulting from the national history and culture. So, the managerial decisions aimed at reforming of social institutions should beviewed through the historical perspective, and the core principle in this process is "do no harm".